Strategi Berkelanjutan Daya Anagata Nusantara (Danantara Indonesia) menjadi Global Player - Mardyanto, Sukma Widi (Universitas Batanghari Jambi, 2025)
Danantara Indonesia is the latest Sovereign Wealth Fund (SWF) established by the Indonesian government to optimize state assets through strategic investments. This study employs a qualitative descriptive approach with a case study method to analyze Danantara’s sustainable strategy in achieving global competitiveness. The study utilizes the Triple Bottom Line (TBL), VRIO Framework, and PESTEL Analysis to evaluate competitive advantages, external factors, and the balance between social, environmental, and economic aspects. The findings indicate that Danantara possesses sustainable competitive advantages in the form of access to strategic assets and government support, yet still faces challenges in governance, transparency, and global market volatility. External factors such as green investment regulations and urbanization trends create opportunities for Danantara to invest in renewable energy, infrastructure, and public services. To strengthen its position, Danantara must implement investment diversification strategies, optimize governance based on the Santiago Principles, and leverage digital technology for risk management and investment decision-making. By adopting sustainability-oriented strategies, Danantara can evolve into a global player in the investment industry while contributing to national economic development. Additionally, partnerships with international investors serve as a strategic step to accelerate Danantara’s global expansion.